Boundary continuity effect on performance of composite beam-slab sub-assemblages at elevated temperature - Zhang, Yao (2022)
The behaviour of composite beam-slab structural system under fire condition has been investigated in the past few decades. However, previous research works mainly focused on isolated beam-slab sub-assemblages. In this paper, the boundary continuity effect on structural behaviour of composite beam-slab sub-assemblages subject to fire is investigated, where three different boundary continuities are considered, namely, internal, edge, and corner composite slab. Six specimens with a single unprotected interior beam were tested to failure, and two aspect ratios of 1 and 1.5 for each boundary condition were included. A total vertical load of 100 kN was applied to each specimen, which was heated by an electrical heating furnace from ambient temperature to 1000 °C within 1 h and maintained at 1000 °C until failure of the specimen occurred. The internal composite slab panel with an aspect ratio of 1 had the longest failure time and the edge composite slab panel with an aspect ratio of 1.5 sustained the longest duration. Finite Element (FE) models of the specimens validated by the experimental results were adopted to study membrane forces in the beam-slab sub-assemblage. Numerical simulations showed that different boundary continuities resulted in different membrane forces, and both the axial and rotational stiffness values in the direction of continuous edges were much greater than those of discontinuous edges for typical composite slabs. Moreover, the authors proposed minor amendments to Bailey-BRE method for calculating the enhanced load capacity at ultimate limit state and showed that the predictions were conservative when compared with test results.